PELAKSANAAN PARATE EKSEKUSI HAK TANGGUNGAN DI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) TANGERANG - Rio Rachmat Effendi (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2020)
The distribution of financing in the form of credit by banks to the public is inseparable from the risk of non-performing loans. In the event of bad credit, goods that are pledged as collateral and have been bound perfectly with a Certificate of Mortgage (HT) in accordance with Law Number 4 of 1996 concerning Mortgage Rights to Land and Objects Related to Land will be sold to cover the debtor's obligations through HT execution parate auction mechanism where creditors can directly apply for HT execution auction to the State Wealth and Auction Service Office (KPKNL) without fiat from the Head of the District Court (PN). The formulation of the problems studied are what are the considerations so that the creditors decide to carry out the HT execution parate auction through the execution parate, how the HT execution parate auction is carried out and what are the obstacles faced in the HT execution parate auction. The research method used is empirical / sociological meaning that this research was conducted with the aim of revealing the reality that occurred in the execution of the HT execution parate auction at the KPKNL Tangerang. The data collection method is done by collecting primary data through observations and interviews with sources as well as secondary data through library research from books, laws and regulations and other publications. In the data analysis method used qualitative data analysis. The creditors' consideration in deciding to carry out the execution parate through an auction mechanism by submitting a direct application to the KPKNL without PN fiat for the sale of HT objects is that the efforts made by the creditors have been maximized in collecting their receivables and the costs are relatively cheaper and the time is fast than if requested through PN preceded by the fiat of the Head of the PN. The obstacles faced in the execution of the HT execution parate auction are the still occupancy of the HT object being auctioned off by the debtor, third parties or their heirs and the fear of prospective auction participants of intimidation from the debtor. In addition, the high limit price of HT objects being auctioned, the location of HT objects that are not strategic so that they are not marketable, marketing of HT objects before the auction is not optimal, local cultural factors that feel reluctant to buy through an auction of HT objects owned by neighbors or figures the local community, negative information received by prospective auction participants from previous buyers / auction winners. With regard to these constraints, creditors should be even more selective in extending credit to their customers both in terms of the prospective debtor's financial capacity and in terms of collateral conditions that are used as collateral for debt repayment. Meanwhile, the Tangerang KPKNL and auction officials should verify more carefully every time there is a request for the execution of HT execution parate auction from creditors to minimize pre-auction and post-auction problems as well as more intensively to provide socialization to creditors about the parate auction for HT execution.